Sistem Pendukung Keputusan dalam Pemilihan Karyawan Terbaik pada PT. Indra Jaya Swastika Cabang Semarang dengan Metode Simple Additive Weighting - Rangga Pratama Yudha; Syafrianto Syafrianto (Jurnal Teknika, 2022)
Decision Support System in Selection of the Best Employees at PT. Indra Jaya Swastika Semarang Branch with the Simple Additive Weighting Method. During the past few years many changes occurred that can affect the company’s business continuity. The ability to pursue these challenges is influenced by the company's ability to manage existing resources, especially Human Resources (HR), namely employees. The role of employees is enormous due to their productivity able to exert influence the company’s quality. So, it is necessary to implement employee motivation at PT. Indra Jaya Swastika Semarang Branch by selecting the best employees to see their work performance. This aims to show the employee's attention and appreciation for the employee's work performance. Decision Support System (DSS) is the right system in this case because it is part of a computer-based information system that can support and facilitate decision making. The DSS model used in this study is Fuzzy Multiple Attribute Decision Making (FMADM), one of the methods chosen is the Simple Additive Weighting (SAW) method. With predetermined criteria, namely teamwork, attendance, performance, attitude and loyality. Also, this system was developed with PHP and MySQL. Based on the results of calculations, A Zaki Fahmi is the best employee with a score of 0.9893. The selection of the best employees with this method is more practical, fast and accurate.